2019
DOI: 10.2174/1874372201913010041
|View full text |Cite
|
Sign up to set email alerts
|

Current Review on Herbs for Derma Care

Abstract: Background: A large number of cosmetic formulations have been developed based on herbs. Indian women have been using herbs such as sandalwood, aloe for skincare protection, since ages. In India, the rich cultural heritage is behind the materials used in cosmetics from the earliest period of medical and cosmetic art. Objective: Continuous application of synthetic compounds on the skin causes many adverse effects such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Furthermore, a large section of Indian consumers prefer herbal cosmetics for their health care[ 125 ]. Hence, it can be concluded that young consumers are in favour of eco-friendly products.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a large section of Indian consumers prefer herbal cosmetics for their health care[ 125 ]. Hence, it can be concluded that young consumers are in favour of eco-friendly products.…”
Section: Discussionmentioning
confidence: 99%
“…These days, a broad variety of substances from various sources are found in cosmetics. The use of botanical ingredients in creams is becoming more common [12]. Nowadays, herbal creams are more often used than synthetic treatments that are sold in stores.…”
Section: Introductionmentioning
confidence: 99%
“…The current study focuses on determining the quality criteria and formulation of a herbal skin treatment for tan regions. 1,2 2. Materials and Methods…”
Section: Introductionmentioning
confidence: 99%